An improved permanent‐magnet synchronous machine sensorless drive based on the fuzzy‐PI phase‐locked loop and the adjustable boundary‐layer FOSMO - Shuaichen Ye; Xiaoxian Yao (IET Power Electronics, 2021)
Abstract This study proposes a variable boundary‐layer full‐order sliding‐mode observer (FOSMO) with a fuzzy proportional plus integral (PI) phase‐locked loop (PLL) for the sensorless control of a permanent‐magnet synchronous machine (PMSM). The sigmoid switching function‐based FOSMO, which includes feedback speed information, is presented and considered as the conventional method. To address the contradiction between the convergence performance and the chatter‐reduction ability of the sliding‐mode control, a fuzzy logic controller (FLC) is introduced to adjust the boundary‐layer thickness according to the estimation error. Furthermore, a real‐time parameter tuning module is integrated into the PI regulator of the conventional PLL to adjust its noise bandwidth. Hence, adverse effects of disturbance and external noise, especially under transient operations, can be eliminated. An overall PMSM sensorless field‐oriented control scheme incorporating the proposed method is designed, and the corresponding experimental platform is constructed. Several groups of comparative experiments reveal that system chatters are largely reduced using the proposed method under both of the high‐ and low‐speed running conditions and the dynamic anti‐interference performance can also be significantly improved under load and speed disturbances. Therefore, the feasibility and effectiveness of the proposed variable boundary‐layer FOSMO + fuzzy‐PI PLL method are validated.